Bone-Forming Peptide-4 Induces Osteogenic Differentiation and VEGF Expression on Multipotent Bone Marrow Stromal Cells - Kim, Mi Eun; Seon, Jong Keun; Kang, Ju Yeon; Yoon, Taek Rim; Lee, Jun Sik; Kim, Hyung Keun (Frontiers in Bioengineering and Biotechnology, 2021)
Bone morphogenetic proteins (BMPs) have been widely used as treatment for bone repair. However, clinical trials on fracture repair have challenged the effectiveness of BMPs and suggested that delivery of multipotent bone marrow stromal cells (BMSCs) might be beneficial. During bone remodeling and bone fracture repair, multipotent BMSCs differentiate into osteoblasts or chondrocytes to stimulate bone formation and regeneration. Stem cell-based therapies provide a promising approach for bone formation. Extensive research has attempted to develop adjuvants as specific stimulators of bone formation for therapeutic use in patients with bone resorption. We previously reported for the first time bone-forming peptides (BFPs) that induce osteogenesis and bone formation. BFPs are also a promising osteogenic factor for prompting bone regeneration and formation. Thus, the aim of the present study was to investigate the underlying mechanism of a new BFP-4 (FFKATEVHFRSIRST) in osteogenic differentiation and bone formation. This study reports that BFP-4 induces stronger osteogenic differentiation of BMSCs than BMP-7. BFP-4 also induces ALP activity, calcium concentration, and osteogenic factors (Runx2 and osteocalcin) in a dose dependent manner in BMSCs. Therefore, these results indicate that BFP-4 can induce osteogenic differentiation and bone formation. Thus, treatment of multipotent BMSCs with BFP-4 enhanced osteoblastic differentiation and displayed greater bone-forming ability than BMP-7 treatment. These results suggest that BFP-4-stimulated cell therapy may be an efficient and cost-effective complement to BMP-7-based clinical therapy for bone regeneration and formation.